A 'study and research path' enriching the learning of mechanical engineering - Bartolomé, Elena; Florensa, Ignasi; Bosch, Marianna; Gascón, Josep (European journal of engineering education, 2019)
Study and research path (SRP) is an inquiry-based teaching format grounded in the Anthropological Theory of the Didactic. One of the specific characteristics of SRP is its task-design basis, which includes explicitly questioning the knowledge at stake in study processes. In this work, we propose general guidelines for the design of SRPs for Engineering courses. We have explored the validity of the SRP methodology for learning Strength of Materials, a key subject in Mechanical Engineering. The use of question-answer maps and the media-milieu dialectics throughout the development of the SRP are discussed, together with the student's perceptions on the new learning process.